Gene expression in Verson’s glands of the fall armyworm suggests their role in molting and immunity - Koo, Jinmo; Chen, Xien; Palli, Subba Reddy (Frontiers in Insect Science, 2023)
Verson’s glands are segmental pairs of dermal glands attached to the epidermis in lepidopteran larvae. They produce macromolecules during intermolt period and empty them during each molt. Morphological, histochemical, developmental, and protein analysis studies have been conducted to determine the functions of Verson’s glands. However, the exact role of Verson’s glands remains unclear. In our previous study, a strain of transgenic fall armyworm, Spdoptera frugiperda expressing green fluorescence protein (GFP) and Systemic RNA interference defective protein 1 (SID-1) from Caenorhabditis elegans was established to improve RNA interference (RNAi) efficiency. Unexpectedly, we found that GFP fluorescence was significantly brighter in Verson’s glands than in other tissues. Also, RNAi efficiency improved more in Verson’s glands than in other tissues. We took advantage of improved RNAi efficiency to explore the function of Verson’s glands. RNA-seq analysis revealed that genes highly expressed in Verson’s glands code for cuticular proteins, hemolymph proteins, molting fluid proteins, and antimicrobial peptides. Injection of dsRNA targeting essential genes interfered with Verson’s gland growth. These studies revealed that Verson’s glands contribute to hemolymph, cuticle, molting fluid, and immune response during molting. These studies also provide useful tools for future research in identifying the physiological role of Verson’s glands in lepidopteran insects.